Anthropogenic Inputs of Terrestrial Organic Matter Influence Carbon Loading and Methanogenesis in Coastal Baltic Sea Sediments - Jilbert, Tom; Cowie, Greg; Lintumäki, Luukas; Jokinen, Sami; Asmala, Eero; Sun, Xiaole; Mörth, Carl-Magnus; Norkko, Alf; Humborg, Christoph (Frontiers in Earth Science, 2021)
Coastal regions globally have experienced widespread anthropogenic eutrophication in recent decades. Loading of autochthonous carbon to coastal sediments enhances the demand for electron acceptors for microbial remineralization, often leading to rearrangement of the sediment diagenetic zonation and potentially enhancing fluxes of methane and hydrogen sulfide from the seafloor. However, the role of anthropogenic inputs of terrestrial organic matter (OMterr.) in modulating diagenesis in coastal sediments is often overlooked, despite being of potential importance in regions of land-use and industrial change. Here we present a dated 4-m sediment and porewater geochemistry record from a eutrophic coastal location in the northern Baltic Sea, to investigate sources of recent carbon loading and their impact on modern diagenetic processes. Based on an end-member mixing model of sediment N/C ratios, we observe that a significant fraction of the late-20th century carbon loading at this location was contributed by OMterr.. Furthermore, analysis of lignin in this material shows depleted ratios of syringyl/vanillyl (S/V) and cinnamyl/vanillyl (C/V) phenols, indicative of enhanced inputs of woody gymnosperm tissue likely from forest industries. The rapid loading of organic matter from combined terrestrial and autochthonous sources during the late 20th century has stimulated methanogenesis in the sediment column, and shoaled the sulfate-methane transition zone (SMTZ) to a depth of 5‒20 cm. Optical parameters of colored dissolved organic matter confirm that OMterr. is actively degrading in the methanogenic layer, implying a role for this material in diagenetic processes. Porewater CH4, SO42- δ13C-DIC, and ∑S2- data suggest that the modern SMTZ is a broad zone in which organoclastic sulfate reduction, methanogenesis and anaerobic oxidation of methane (AOM) co-occur. However, fluxes of CH4 and SO42- show that rates of these processes are similar to other marine locations with a comparably shallow SMTZ. We suggest that the shallow depth of the modern SMTZ is the principal reason for high observed diffusive and ebullitive methane fluxes from sediments in this area. Our results highlight that anthropogenic activities lead to multiple pathways of carbon loading to coastal sediments, and that forest industry impacts on sedimentation in the northern Baltic Sea may be more widespread than previously acknowledged.